Change of heart [large type] - Walsh, Courtney, 1975- (Center Point Large Print, 2016)
"The Valentine Volunteers refuse to let Evelyn's divorce from a disgraced Colorado senator destroy her and ask her to use her artistic talent to reimagine the city's iconic lamppost hearts, forcing her to work closely with a man who was in love with her before she sacrificed her dreams to become the perfect politician's wife"--